HUMAN NATURE AND CULTURE ON THE PROGRESS OF EDUCATION - sambas Sugiarto; Firman; Riska Ahmad (Yayasan Citra Dharma Cindekia, 2021)
Human nature and culture towards the advancement of education in Indonesia have a very important role and function in it. So that humans and culture are the main factors that become the benchmark of success in advancing education in Indonesia. This study aims to make education in Indonesia progress and develop the abilities of every child who is in the process of advancing the nation and state. This study uses a qualitative approach to the category of literature (Library Research). Humans and culture are inquisitive creatures who are always curious about various things. Not only do they want to know about everything that is outside themselves, humans also try to find out about who they are. In real life, humans have many differences, both physical appearance, social strata, habits and knowledge.